Academic freedom in Scandinavia: has the Nordic model survived?. Issue 1 (2nd January 2023) - Karran, Terence; Beiter, Klaus; Mallinson, Lucy
ABSTRACT: The Scandinavian states have international reputations for promoting social democratic ideals, which have long been manifest in Nordic universities, e.g. legal protection for academic freedom and university studies free of charge. However, Nordic governments have made new h.e. laws, thereby changing university autonomy and management structures, leading to greater involvement by external personnel in university governance, and reduced academic freedom for academic staff. Utilizing legal data, and a survey of+5, 000 academics from the EU states, this paper compares the protection for academic freedom in Denmark, Finland, Norway and Sweden. The de jure analysis shows that a single Nordic grouping is not apparent, but that there are two distinct Scandinavian cohorts. The de facto analysis reveals differences between the Nordic nations and other EU states but does neither confirm the Nordic model nor substantiate two regional cohorts identified in previous research and in the de jure analysis.